Case Report of a New Coupler for Round Window Application of an Active Middle Ear Implant. Issue 10 (December 2018) - Lenarz, Thomas; Zimmermann, Denise; Maier, Hannes; Busch, Susan
Abstract : Objectives: To evaluate feasibility, surgical handling, audiological outcome, and coupling efficiency of a new coupler (custom-made device) for an active middle ear implant. Patient: Revision surgery after implantation of an active middle ear implant in a 66-year-old male patient with mixed hearing loss. Intervention: Prosthetic hearing rehabilitation with a new coupler for round window application. Main Outcome and Results: The patient obtained good speech perception in quiet (word recognition scores 80%; Freiburg monosyllables) and noise (−3.3 dB SNR; Oldenburg Sentence Test). The effective gain with the Hannover coupler improved at frequencies > 0.5 kHz compared with the values reported for other round window (RW)-coupling modalities. Conclusion: The coupler provides a feasible option for the RW application of the middle ear implant actuator. The spring concept of the coupler needs to be improved to further standardize RW-coupling and improve coupling efficiency at low frequencies (0.5 kHz).